Analysis of the implementation character education in elementary schools based on the pillars of character education - Jenny Indrastoeti Siti Poerwanti; Sri Marmoah; Supianto Supianto; Sukarno Sukarno; Siti Istiyati (Universitas Sebelas Maret, 2025)
Educating the characters is the process of giving, integrating and, forming teachers' characters for students. In the implementation of the education of characters in the school, the commitment of all the school's residents is required to implement it in a coherent manner. The study aims to analyse the education of characters in two elementary schools base on six pillars of the character, namely trustworthiness, respect, responsibility, fairness, caring, and citizenship. This research method uses qualitative descriptive which describes the implementation of character education in elementary schools. Data collection methods use interviews, observations, and document analysis. Data analysis involves three steps: data reduction, data presentation, and retrieval. The results of this study indicate that character education related to trust, respect, responsibility, fairness, care, and citizenship, has been implemented through various activities, including classroom learning, extracurricular activities, habituation, and collaboration with the local community. The significance of the effective education of characters can improve the quality of overall education. When students have a good personality, they will learn more easily, will be more disciplined and will be able to work together better in a group.